Primary prostate synovial sarcoma: A case report and review of literature. (July 2022) - Hou, Dongsheng; Wang, Xiaotong; Xia, Qiuyuan; Zong, Yuanyuan
Abstract: Prostate synovial sarcoma (SS) is extremely rare. We report a case of prostate SS diagnosed using fine-needle biopsy. The following findings were found: The serum prostate specific antigen level was low, magnetic resonance imaging shows an irregular soft tissue mass in the right posterior part of the prostate, and computed tomography examinations did not reveal any tumor at other parts of the body. Microscopy showed that the tumor cell morphology was densely arranged by interwoven short strands of deep-stained nuclear spindle cells. Immunohistochemical tests were positive for SS18-SSX and SSX. Molecular testing showed that SS18 break-apart Fluorescence In Situ Hybridization (FISH) results were positive, and a comprehensive analysis of this case was performed. Nine cases of prostate SS reported in the English literature were reviewed. In addition, the differential diagnosis, clinical treatment, and clinical prognosis of prostate SS are comprehensively described.